Motivasi Masyarakat dalam Budidaya Kopi Pesisir di Desa Pucangan Kecamatan Ambal Kabupaten Kebumen - Ana Fitrotun Nisa; Suminah Suminah; Eny Lestari (AGRITEXTS: Journal of Agricultural Extension, 2020)
Coffee is one of the plantation commodities results that have high economic value among other plantation crops. One of them is the coastal coffee. Coastal coffee is coffee that is cultivated in coastal areas with a height of fewer than 15 meters above sea level. This study aimed to analyze the level of motivation villagers, know the level of the motivation forming factors villagers and analyze the effect of motivation forming factors to the motivation villagers in coastal coffee cultivation in Pucangan Village Ambal District Kebumen Regency. This study uses a quantitative method. The location is chosen because it is only the village that grows coastal coffee. Samples are  taken using a simple random sampling technique with the Slovin formula amount of 55 people.   The data is analyzed using multiple linear regression IBM SPSS Statistics 25. The results show that most of the Pucangan villagers have high motivation in coastal coffee cultivation, the level of motivation forming factors are the non-formal education is low, lower-middle-income villagers, the role of counselor and social environment are high, facilities and infrastructures are available in large quantities. The results of multiple linear regression analyses show the effect of motivation villagers significantly are non-formal education, the role of educator, social environment, facilities and infrastructure, whereas no significant effect on earnings. From the results of these studies is suggested the government help to resolve problems through cooperation assistance from the department of agriculture extension as Kebumen District to more intensively so that the coffee plant is not only a byproduct plant and has economic value.